THE CONTRIBUTION OF PALM OIL FARMERS' INCOME TO FARMERS HOUSEHOLD NEEDS (Study in Alue Ambang Teunom Village, Aceh Jaya District) - Fitri Asni; Aswin Nasution (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Alue Ambang Village is one of the villages in Teunom District, Aceh Jaya Regency, where the majority of the population is highly dependent on oil palm plantations. Unstable palm oil prices can affect farmers' income. This study aims to determine the contribution of oil palm income to the household needs of farmers. Of the 53 respondents who used the results of the study showed that income from oil palm can contribute to farmer households in Alue Ambang Village with a ratio of 1.1 where 62% of farmers can be fulfilled from their oil palm plantations while 38% of oil palm farmers whose income is not sufficient to meet their needs household.